Konservasi Energi Panas Sisa Proses Geothermal Power Plant - Hanif Putera; Harun Al Rosyid (Jurnal Teknologi dan Rekayasa Manufaktur, 2021)
Current technology advances situation are inline with electrical energy demand, but this is not inline with the availability of resources that produces electrical energy, in order to that it requires an energy conservation to increase efficiency and optimization of a power plant so it can support increasing of electricity demand. This paper gives a feasibility analysis of heat energy conservation from geothermal power plant waste heat as a main power plant. With using Organic Rankine Cycle(ORC) System with Iso-Butene as a working fluid, by calculating heat balance of the ORC cycle, until getting enthalpy and entropy value of the system, thus we can calculating the energy can produce by expansion turbine which drive the generator, with result of this paper is the additional energy produce by ORC system..